2023
DOI: 10.1002/chir.23579
|View full text |Cite
|
Sign up to set email alerts
|

Comparative rotatory power of bent and twisted polyynes

Sophia Sburlati,
Afton Gustafson,
Bart Kahr

Abstract: Linear polyynes of the formula C18H2 (symmetry D∞h) were bent in silico by progressively introducing CCC angles less than 180°. The bent structures (symmetry C2v) were then twisted by introducing torsion angles across the CCCC segments by as much as 60°. The gyration tensors of these 19 structures (linear, bent, and twisted) were computed by linear response methods. Bending is massively generative of optical activity in oriented structures, even achiral structures, whereas twisting in conjunction with ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…We showed that curvature is generative of OA, even for planar, bent carbon chains C 18 H 2 . [75] 4 1 may be more responsive than 3 1 because it has a larger integrated curvature. Increased curvature supports larger magnetic dipole transition moments.…”
Section: Computed Gyration Tensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that curvature is generative of OA, even for planar, bent carbon chains C 18 H 2 . [75] 4 1 may be more responsive than 3 1 because it has a larger integrated curvature. Increased curvature supports larger magnetic dipole transition moments.…”
Section: Computed Gyration Tensorsmentioning
confidence: 99%
“…The electric dipole-magnetic dipole contribution dominates as we have seen before in extensively π-conjugated systems. [32,33,36,75] Although the approximately S 4 symmetric 4 1 is achiral in its ground state, it has OA when oriented. The absolute eigenvalues of the gyration are nearly twice as great as those of 3 1 , its chiral stereoisomer, equating to a comparable OA.…”
Section: Computed Gyration Tensorsmentioning
confidence: 99%